Domestic Violence and the Islamic Tradition: Ethics, Law, and the Muslim Discourse on gender by Ayesha S. Chaudhry (New York: Oxford University Press, 2013. 258 pages.) (American Journal of Islam and Society, 2015)
The polyvalent Qur’anic text lends itself to multiple interpretations, dependingupon one’s presuppositions and premises. In fact, Q. 3:7 distinguishesbetween muḥkam (explicit, categorical) and mutashābih (metaphorical, allegorical,symbolic) verses. As such, this device provides a way for reinterpretingverses that outwardly appear to be problematic – be it in the area ofgender equality, minority rights, religious freedom, or war. However, manyof the verses dealing with legal provisions in such areas as devotional matters,marriage, divorce, child custody, inheritance and bequest, and specific punishmentsappear to be unequivocal, categorical, and explicit. As such, scholarshave devised certain hermeneutical strategies to situate and contextualizethese verses in a particular socio-historical context, as well as to emphasizethat they were in conversation with the society to which the Qur’an was revealedand thereby underlining the “performative” (p.15) nature of the relationshipbetween the Qur’an and the society.No verse is more problematic, in the sense that it offends contemporarysensibilities and is quite difficult to reconcile with an egalitarian worldviewwhen dealing with gender issues, than Q. 4:34, which allows the husband todiscipline his wife if he deems her guilty of nushūz (e.g., disobedience, intransigence,sexual lewdness, aloofness, dislike or hatred of himself). AyeshaChaudhry undertakes a study of this challenging verse by engaging the corpusof literature in Arabic from the classical period to the seventeenth century; shealso includes Urdu and English sources for the post-colonial period.She starts off by relating her personal journey from a state of discomfortand puzzlement when she first came across this verse in middle school to adefensive posture in trying to convince herself by invoking the Prophet’scompassion toward his wives and in cherishing the idea that the Qur’an gavemore rights to women than either the Hebrew Bible or the New Testament.She began a more rigorous and nuanced study of this verse after equippingherself with the necessary academic tools and analytic skills during her universitystudies. Frustrated with the shallow responses and the scholars’ circumspectionas regards any creative and novel reading of the verse for fearof losing their status in the community, she decided to do so herself with thehope of discovering views that would promote an egalitarian reading. But ...